4-H Livestock Judging: Introduction and Leader's Guide - Chad Carr; Justin Crosswhite; Amanda Johnson (EDIS, 2012)
This document is an educational guide. It serves as a curriculum resource within the Florida 4-H program, specifically designed for teaching livestock judging to young people aged 11-18. The guide emphasizes the development of various life skills through judging activities, such as communication, decision making, and organizational skills, while also aiming to boost confidence and self-esteem among participants.